Antimicrobial resistance of zoonotic bacteria isolated from shrimp aquaculture environments in Selangor, Malaysia - Devadas, S.; Zakaria, Z.; Shariff, M.; Bhassu, S.; Karim, M.; Natrah, I. (Elsevier B.V., 2025)
Intensive aquaculture farming has caused an increase in antimicrobial use (AMU) and the emergence of antimicrobial resistance (AMR). Malaysia is the ninth-largest shrimp exporter in the world. Nonetheless, the available data on AMR in shrimp aquaculture is insufficient to support efforts to combat the issue effectively. This study analyses the antimicrobial susceptibility profile and multiple antibiotic resistance (MAR) indexes of Vibrio parahaemolyticus, Escherichia coli and Salmonella in shrimp aquaculture environments in Selangor State. In total, 47 bacterial isolates, consisting of 33 (70.2 %) V. parahaemolyticus, 12 (25.5 %) E. coli and two (4.3 %) Salmonella, were isolated. Other than the intrinsically resistant-related classes of antibiotics, the V. parahaemolyticus isolates showed the top five highest percentages of resistance towards ampicillin (81.8 %, n = 27), followed by erythromycin (69.7 %, n = 23), neomycin (60.6 %, n = 20), kanamycin (54.5 %, n = 18) and ciprofloxacin (39.4 %, n = 13). Likewise, the E. coli showed resistance towards ampicillin (66.7 %, n = 8), followed by 58.3 % (n = 7) to azithromycin and cephalexin and 41.7 % (n = 5) to tetracycline, sulfamethoxazole/trimethoprim and neomycin. Thirty (63.8 %) isolates exhibited a MAR index >0.2, while 31.9 % (n = 15) were classified as multidrug-resistant (MDR) and demonstrated seven types of resistance patterns. The AMU and other potential sources may contribute to the presence of AMR bacteria in aquaculture. Therefore, enhanced AMU and AMR monitoring and investigation into genome characteristics are crucial to better understanding and minimizing the risk of AMR in shrimp aquaculture, particularly in Malaysia, with implications for global aquaculture practices.